Family Literacy of Baduy Tribe: an Ethnographic Study - Ila Rosmilawati; Dadan Darmawan (Universitas Negeri Padang, 2020)
The purpose of this ethnographic study was to reveal the family literacy practices of Baduy tribe at Lebak Regency, Banten Province. Family literacy in this paper refers to an intergenerational learning in in Baduy tribe families, which include how family learns, uses reading and writing activities to do daily task, and other literacy activities to maintain family relationship. Family literacy in Baduy is called intergenerational learning in which the learning method that is practiced in families and communities leads to the creation of a process of cultural and educational transformation in a society. This study utilizes ethnographic approach by conducting interviews with sixteen families (father and mother) and eighteen children and youth. Data analysis includes the four stages of ethnographic data analysis, namely domain, taxonomy, component and theme analysis. The results showed that family literacy in the Baduy tribe last a lifetime, starting from children aged 7 days to 10 years. The literacy activities of the Baduy family cannot be separated from the their culture and beliefs. This culture is passed down from generation to generation with an intergenerational learning approach, it is the process of delivering literacy that is practiced directly within the family.